Assessment of derangement in biochemical profile in primary open angle glaucoma patients presenting at a tertiary care hospital - Zuhra, Fatima Tuz; Khattak, Mehnaz; Nadeem, Sana; Atzaz, Noreen; Khalid, Attika; Saeed, Sami (Journal of Rawalpindi Medical College, 2022)
Objective: To assess the changes in high sensitivity C Reactive protein (hs-CRP), serum cholesterol, uric acid, creatinine, bilirubin and ALT in patients of primary open angle glaucoma. Material and methods: Comparative cross-sectional study conducted between April 2021 and October 2021 at departments of Ophthalmology and Pathology, –removed for blind review—-44 POAG patients and 54 healthy controls volunteered to participate in the study. POAG was diagnosed as per criteria. Venous blood was drawn for analysis of serum cholesterol, uric acid, creatinine, bilirubin, ALT and hs-CRP. hs-CRP was performed on ELISA plate reader Platos R496 while spectrophotometric analysis of serum uric acid, creatinine, and cholesterol was carried on Beckman Coulter AU-700. Results: Mean hemoglobin (Hb), Total leukocyte count (TLC), serum urea, creatinine, uric acid, ALT, bilirubin, cholesterol and HbA1c were 12.80 ±1.50g, 8.88±1.92 mm3, 5.95±5.47 µmol/l, 92.19±21.81 µmol/l, 305.85±79.92 mmol/l, 34.31±18.26 IU/L, 9.26±3.11 µmol/l, 5.18±0.96 mmol/l,6.70±1.28 %respectively whereas the Mean IOP in POAG patients was 28mmHg, mean CCT was 516.6 µm, and mean vertical CDR was 0.6. High frequency of hs-CRP positivity (50 percent) was reported in our patients. Significantly lower uric acid levels were observed in primary open angle glaucoma patients versus controls ie 305.85±79.92 mmol/l vs 344.36±37.24 mmol/l (P value < 0.05). Serum creatinine was significantly different between mild and severe groups i.e. 88±14.7 vs 113.1±32.4. (p value <0.001*) Conclusion: High frequency of hs-CRP positivity and low uric acid levels suggest the presence of para inflammation in patients of POAG. Key words: Primary open angle glaucoma (POAG), intraocular pressure (IOP), high sensitivity CRP (hs-CRP), uric acid (UA)